S-box Construction on AES Algorithm using Affine Matrix Modification to Improve Image Encryption Security - Alamsyah Alamsyah; Budi Prasetiyo; Yusuf Muhammad (Universitas Negeri Semarang, 2023)
Abstract.Purpose: In this study, the AES algorithm was improved by constructing the S-box using a modified affine matrix and implementing it so that there was an increase in security in image encryption.Methods: The method used in this study starts from selecting the best irreducible polynomial based on previous studies. The irreducible polynomial chosen is . With this irreducible polynomial, an inverse multiplicative matrix is formed. The formed inverse mutiplicative matrix is implemented in the affine transformation process using the best 3 affine matrices based on previous research and 8-bit additional constants using AES S-box. This formulation produces 3 different S-boxes, i.e., S-box1, S-box2, and S-box3. Finally, the resulting S-boxes are implemented to carry out the image encryption process and are tested for their security level.Result: The test results show an increase in image encryption security compared to previous studies. The increase in security occurred at the entropy value of 7.9994 and the NPCR value of 99.6288%.Novelty: The novelty of this paper is the improvement of the S-box construction which is implemented in image encryption resulting in increased security in image encryption.